2005
DOI: 10.1177/0887403404267386
|View full text |Cite
|
Sign up to set email alerts
|

Charitable Choice and Prison Ministries: Constitutional and Institutional Challenges to Rehabilitating the American Penal System

Abstract: The influence of faith-based prison ministries in the American criminal justice system is examined in the context of the Bush Administration’s efforts to subsidize the social service activities of religious organizations. Studies on the efficacy of prison ministries in rehabilitation are inconclusive; however, some evidence suggests that these programs may be effective in reducing rates of recidivism and improving prison behavior and inmates’ adjustment to life after incarceration. Preliminary reports have pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Anything less than this type of systematic approach is likely to leave current debates about faith-based programs at a standstill, with proponents accepting "on faith" that faith-based programs are effective and opponents rejecting, on similar grounds, that assessment. Of course for some critics, effectiveness is irrelevant-in their view there is a constitutional requirement that church and state be separated, especially where taxpayer dollars are concerned (McDaniel et al, 2005). As with many policy debates involving constitutional or philosophical differences of opinion, research cannot be the ultimate arbiter, but it can help place such debates on a firmer foundation.…”
Section: Resultsmentioning
confidence: 98%
“…Anything less than this type of systematic approach is likely to leave current debates about faith-based programs at a standstill, with proponents accepting "on faith" that faith-based programs are effective and opponents rejecting, on similar grounds, that assessment. Of course for some critics, effectiveness is irrelevant-in their view there is a constitutional requirement that church and state be separated, especially where taxpayer dollars are concerned (McDaniel et al, 2005). As with many policy debates involving constitutional or philosophical differences of opinion, research cannot be the ultimate arbiter, but it can help place such debates on a firmer foundation.…”
Section: Resultsmentioning
confidence: 98%
“…By meeting state standards and reporting requirements, Teen Challenge would be forced to adopt the biological model of treatment favored by the state and the larger scientific community (Mellor, 1996). The controversy was settled with the passage of the 1997 Texas legislation establishing an alternative certification system exempting faith-based programs from regular licensing regulations (McDaniel, Davis, & Neff, 2005).…”
Section: Characteristics Of the Clinical Staffmentioning
confidence: 99%
“…This finding also supports a previous rmding by Koenig (1995) that states that the more an inmate attends a Bible study, the less-likely they are to be classified to a medium-security facility or as a high-risk inmate within a particular facility. Although such results seem to be promising, McDaniel et al (2005) found in a review of literature on the benefits of faithbased programming that recidivism rates only seemed to drop when inmates were on the middle-to-high side of the attendance rates, thus making explicit benefits less clear to identify.…”
Section: Benefits Of Faith-based Organizationsmentioning
confidence: 95%
“…This controversy is due to the billions of dollars that certain faith-based groups can receive for their work when the benefits of said work are not entirely clear and/or certain (McDaniel, Davis, & Neff, 2005). Although many uncertainties remain about the benefits that these faith-based programs can provide, there is strong support for the further implementation of these programs.…”
Section: Bush Administration Faith-based Initiativesmentioning
confidence: 99%
See 1 more Smart Citation